STUDENTS’ PERCEPTION OF ENGLISH CLUB TOWARDS THEIR SPEAKING SKILLS - Ramadhani, Putri; Munir, Munir; G., Hasriani (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2025)
This study aims to describe students' perceptions of English Clubs towards their speaking skills. Using a qualitative method, data were collected through in-depth interviews with high school students actively participating in English Club activities and validated with documentation of their English grades. The findings reveal that most students perceive English Clubs positively. They view these clubs as supportive spaces to practice speaking freely, boost their confidence, and broaden their understanding of English usage in daily life. Besides the perceived benefits, the study also identifies challenges faced by students, such as anxiety and a lack of courage to speak in public. Nevertheless, the supportive environment provided by English Clubs helps students feel more comfortable and motivated to continue learning. This research offers insights into how students perceive their experiences in English Clubs and highlights the potential of such clubs to enhance speaking skill development.Keywords: English Club, speaking skill, student perception, language learning, learning experience